2021
DOI: 10.3389/fmicb.2021.671676
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Local Dynamics, and Genomic Characteristics of ESBL-Producing Escherichia coli Isolated From Specimens of Hospitalized Horses

Abstract: Previous research identified veterinary clinics as hotspots with respect to accumulation and spread of multidrug resistant extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (EC). Therefore, promoting the prudent use of antibiotics to decrease selective pressure in that particular clinical environment is preferable to enhance biosecurity for animal patients and hospital staff. Accordingly, this study comparatively investigated the impact of two distinct perioperative antibiotic prophylaxis (PAP) r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 42 publications
(74 reference statements)
2
10
0
4
Order By: Relevance
“…Implementation of an effective infection prevention protocol in the equine hospital in the current study might have prevented or reduced the dissemination of antimicrobial-resistant bacteria and ARGs to hospitalised horses. However, previous studies using culture-based or PCR techniques have shown that antimicrobial-resistant E. coli bacteria increase in the faeces of horses, independent of antimicrobial administration, within days of hospitalisation [55][56][57][58][59][60]. One study compared the duration of faecal shedding of resistant E. coli after antimicrobial treatment between hospitalised horses and non-hospitalised horses [61].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of an effective infection prevention protocol in the equine hospital in the current study might have prevented or reduced the dissemination of antimicrobial-resistant bacteria and ARGs to hospitalised horses. However, previous studies using culture-based or PCR techniques have shown that antimicrobial-resistant E. coli bacteria increase in the faeces of horses, independent of antimicrobial administration, within days of hospitalisation [55][56][57][58][59][60]. One study compared the duration of faecal shedding of resistant E. coli after antimicrobial treatment between hospitalised horses and non-hospitalised horses [61].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless previous research revealed veterinary clinics as ‘hotspots’ for local MDR pathogen accumulation and transmission (Apostolakos et al., 2017 ; Kauter et al., 2021 ; Walther et al., 2018a ; Wright et al., 2005 ). As our results are in line with recent reports, the development of appropriate hygiene strategies that take into account the special challenges of equine medicine (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, infected laparotomy incisions were infected significantly more often with ESBL‐E and A. baumannii than the infected wounds of injured horses. The protection of the incisional wound from residing MDRP from the mucosal surfaces and/or the environment seems crucial to prevent SSI, especially because earlier studies identified 10.7% of admitted horses being positive for ESBL‐E and 3.5% for MRSA (Kauter et al., 2021 ; Walther et al., 2018a ; Walther et al., 2018b ). A simple wound covering was placed after the laparotomy and renewed after recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial isolates investigated in this study were identified by standard microbiological procedures as previously described [ 52 , 53 , 54 , 60 , 61 , 62 ]. In brief, the samples were analysed by aerobic cultivation after direct inoculation on suitable agar plates (all agar purchased from Oxoid, Wesel, Germany).…”
Section: Methodsmentioning
confidence: 99%